PEMETAAN WILAYAH PRIORITAS PENINGKATAN AKSESIBILTAS SANITASI DALAM PERSPEKTIF RENCANA STRATEGIS PEMBANGUNAN SANITASI DI PROVINSI JAWA TENGAH - Maryono, Maryono (Universitas Diponegoro, 2010)
Choosing for priority areas in efforts to improve sanitation usually determined by various considerations such as technical, economic, social, cultural, community empowerment, and physical environment in the study area. Consideration of the technical aspects will formulate about the availability of infrastructure services. Socioeconomic considerations explain poverty, income per capita. Socio-cultural considerations and community empowerment to explain about the culture, habits and the willingness and ability of communities to bersaniter. While the physical environment considerations explain the advantages and disadvantages of natural physical region, including the potential occurrence of natural disasters and disturbances. this study is conducted to analysis on the Priority sanitation improvement that combines of social aspects such as economic considerations and technical aspect such as availability of facilities / infrastructure sanitation